2023
DOI: 10.3390/polym15071692
|View full text |Cite
|
Sign up to set email alerts
|

Developing Performance-Based Mix Design Framework Using Asphalt Mixture Performance Tester and Mechanistic Models

Abstract: This paper proposes a performance-based mix design (PBMD) framework to support performance-related specifications (PRS) needed to establish relationships between acceptable quality characteristics (AQCs) and predicted performance, as well as to develop fatigue-preferred, rutting-preferred, and performance-balanced mix designs. The framework includes defining performance tests and threshold values, developing asphalt mix designs, identifying available performance levels, conducting sensitivity analysis, establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the realm of pavement engineering, recent studies have explored innovative approaches to incorporate recycled materials and by-products [ 13 , 14 ], with a specific focus on enhancing the sustainability and performance of asphalt mixtures. Dong et al investigated the utilization of recycled rubber and reported improvements in asphalt mixtures’ flexibility and fatigue resistance [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of pavement engineering, recent studies have explored innovative approaches to incorporate recycled materials and by-products [ 13 , 14 ], with a specific focus on enhancing the sustainability and performance of asphalt mixtures. Dong et al investigated the utilization of recycled rubber and reported improvements in asphalt mixtures’ flexibility and fatigue resistance [ 15 ].…”
Section: Introductionmentioning
confidence: 99%